Finding and fixing food system emissions: the double helix of science and policy - Rosenzweig, Cynthia; N Tubiello, Francesco; Sandalow, David; Benoit, Philippe; N Hayek, Matthew (Environmental research letters, 2021)
Improving estimates of greenhouse gas (GHG) emissions from food production, supply, consumption, and disposal is fundamental to identifying effective policy solutions. Through broader awareness of the food-climate nexus, climate mitigation as well as resilience can be enhanced. However, work is needed to address knowledge gaps, promote better policies and improve public understanding of issues related to the food system and climate change. The intention of this paper is not only to highlight the need for better scientific understanding of the processes through which GHGs are emitted—from production to processing, from supply chains and retail to food preparation and waste (figure 1)—but also to integrate science and policy in order to scale up impact on climate change action.